PERANCANGAN MOTION COMIC SEBAGAI MEDIA PROMOSI WISATA SEJARAH KOTA LAMA SEMARANG - Tri Widadijo, Wahju; Santoso, Therryous Batistuta (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2024)
Semarang, the capital of Central Java, is a culturally diverse city that is rich in well-preserved cultural heritage. One of its popular historical cultural destinations is Kota Lama Semarang / Semarang Old City, an area recognized as a national cultural heritage site. However, the tourism promotion of Kota Lama Semarang still relies on conventional media like flyers, brochures, posters, and social media, which lack targeted content for urban teenagers. To address this, Motion Comic media is proposed as a new approach to promote the captivating tourism of Kota Lama Semarang, focusing on its rich historical value. Motion Comic combines visual, movement and sound to engage teenagers and help them appreciate the history and culture of Kota Lama Semarang. By utilizing this media, it is hoped that teenagers will develop an interest in visiting Kota Lama Semarang while also preserving and appreciating the history of Kota Lama Semarang